The Moderating Role of Green Price on the Influence of Environmental Awareness and Product Uniqueness on Ecoprint Product Purchase Decisions in Malang Regency - Nur Ajizah; Nur Hidayati; Nuril Khikmawati; Nur Riski Rohmayanti (Universitas Yudharta Pasuruan, 2025)
The purpose of this research Introduction is to identify the extent to which the moderation role of green price influences the relationship between environmental awareness and product uniqueness with purchasing decisions of ecoprint products in Malang Regency. This study employs a quantitative research method, Method; The sampling technique utilizes purposive sampling with a total population of 103 respondents. Data analysis was conducted using multiple linear regression with the assistance of Statistical Package for the Social Science (SPSS) version 25. Results; Based on the research findings, environmental awareness has a significant effect on purchasing decisions, while product uniqueness does not have a significant effect on purchasing decisions. Additionally, green price is proven to moderate the relationship between environmental awareness and purchasing decisions as well as the relationship between product uniqueness and purchasing decisions. Conclusion; The study concludes that green price plays an important moderating role in strengthening the influence of environmental awareness and product uniqueness on purchasing decisions for ecoprint products in Malang Regency.